KONSEPSI ISLAM DALAM PENEGAKAN KEADILAN - Sangkot Nasution (Universitas Islam Negeri Sumatera Utara Medan, 2017)
Justice has always been regarded as the cardinal virtue and is a moral obligation that binds members of society. Justice is a goal to be achieved by law. Justice in this case implies